Experiment as methods of student’s methods of mathematical research activity - Balčiūnas, Sigitas; Freibergaitė, Daiva (Lietuvos matematikos rinkinys, 2002)
The article deals with the mathematical experiment method on the basis of the constructivist theory. The types of experiment are illustrated by mathematical samples at school. The samples of mathematical experiments out by students are displayed.